How do you simplify (sqrty-5)^2?

2 Answers
Apr 11, 2018

Foil and add like terms

Explanation:

I really hope that you know how to foil so I am not going to explain it but once you expand you get (sqrty-5)(sqrty-5). If you did not know when you multiply two roots the cancel and the middle number stays the same. So when you foil you should get y-5sqrty -5sqrty+25 which simplifies to y-10sqrty+25.

Apr 11, 2018

y-10sqrty+25

Explanation:

Using the FOIL method, you can multiply the two terms inside the parenthesis together.

(sqrty-5)^2=(sqrty-5)(sqrty-5)

F means "first terms."

sqrty*sqrty=sqrty^2=y

I means "inner terms."

-5*sqrty=-5sqrty

O means "outer terms."

sqrty*-5=-5sqrty

Finally, L means "last terms."

-5*-5=25

Add your four results together and simplify to complete the foil.

y+(-5sqrty)+(-5sqrty)+25

=y-10sqrty+25

That is the expanded form.